How Do Non-driving-related Tasks Affect Engagement Under Highly Automated Driving Situations? A Literature Review - Jaussein, Marie; Lévêque, Lucie; Deniel, Jonathan; Bellet, Thierry; Tattegrain, Hélène; Marin-Lamellet, Claude (Frontiers in Future Transportation, 2021)
Driving automation has become a trending topic over the past decade, as recent technical and technological improvements have created hope for a possible short-term release of automated vehicles. Several research teams have been exploring driver performance during control transitions performed under highly automated driving (i.e., while resuming manual driving, when facing a critical situation for instance). In this paper, we present a state of the art of studies dealing with control transitions as well as the concept of non-driving-related task (NDRT) engagement. More specifically, we aim to provide a global view on how task engagement is investigated in the literature. Two main utilisations of task engagement emerged from our literature review: its manipulation as independent variable to vary the driver’s engagement state before a control transition, and its measurement as dependant variable to compare its variation to driving behaviour variables during a control transition. Furthermore, we propose a new perspective on control transition, which was so far studied through a techno-centric approach; research works were indeed designed in function of the system state. Our article suggests a more cognitive-centred view by taking in account the evolution of engagement mechanisms along control transition stages. Finally, we provide a categorisation of engagement mechanisms’ variables involved during these different stages, with a view to facilitate future investigations on the driver’s engagement state during this crucial phase of highly automated driving.